Arquitetura de alta disponibilidade para Firewall e IPS baseada em SCTP - Lopes Filho, Edmo (2008)
The growth and proliferation of computer networks allow businesses efficiently to communicate with their own components as well as with their business partners, customers, and suppliers. However, the flexibility and efficiency provided by such systems come with increasing risks, including disruption of services. To address the security issues, network and security managers, among other options, often turn on network policy and access control management such as firewall and IPS (Intrusion Prevention Systems) protection. The dissertation addresses one of the three basic requirements of security management programs: Availability and proposes a new architecture for firewall and IPS high availability based on the SCTP protocol.